ANALISIS KESALAHAN SISWA SMK DALAM MENYELESAIKAN SOAL MATERI GEOMETRI RUANG - Wanda Sukma Azhar; Eka Senjayawati (IKIP Siliwangi, 2021)
Mathematics is closely related to real lift. However, there are still many students who make mistakes in learning mathematics, this is because students still think that learning mathematics is difficult. The purpose of this study was to analyze the students errors in solving spatial geometry problems. The subject af this research wa conducted at SMK TI Garuda Nusantara in class XII TKJ with a sample of 12 students. The method used is acase study, and the form of data collection is to provide 4 test questions on different indicators for each question. From the results of this study, the results of the highest student error were on the indicator calculating the distance between line to line with a percentage of 70,6% and the lowest student error results on the indicator calculating the angle size with a percentage of 17,2%.